The endogean beetle fauna of the Marganai-Oridda-Valle del Leni area (SW Sardinia), with description of seven new species of Staphylinidae Leptotyphlinae (Coleoptera) - Fancello, Luca; Hernando, Carles; Leo, Piero (Zootaxa, 2009)
Twenty-six species of endogean beetles are recorded from the Marganai-Oridda-Valle del Leni area, belonging to six different families: Carabidae (Typhloreicheia holdhausi Magrini, Fancello & Casale, 2006, T. leoi pilosa Magrini & Fancello, 2007, T. tanit Leo, Magrini & Fancello, 2005), Leiodidae [Bathysciola damryi (Abeille de Perrin, 1881)], Staphylinidae [Eudesis aglena Reitter, 1882, E. minima Binaghi, 1948, Mayetia sp., Trimium amplipenne Reitter, 1908, Tychobythinus dentimanus (Reitter, 1884), Tychus sp., Pselaphostomus sp., Phloeocharis ichnusae Dodero, 1900, Octavius raymondi Saulcy, 1878, O. sardous Coiffait, 1965, four new species of Entomoculia, three new species of Leptotyphlus], Zopheridae (Langelandia reitteri Belon, 1882, Lyreus septemstriatus Fancello & Leo, 1991), Curculionidae (Torneuma sp.) and Raymondionymidae [Alaocyba carinulata Perris, 1869, Raymondiellus sardous sardous (Perris, 1869)]. One species (Langelandia reitteri) is W-Mediterranan, one is a Sardo-Corsican endemic (Tychobythinus dentimanus), the remaining 24 species are all Sardinian endemics and 16 of these are strictly localized within the study area or restricted to SW Sardinia. The following species of Staphylinidae Leptotyphlinae are described: Entomoculia villascemae sp. nov., E. carbonaria sp. nov., E. shardana sp. nov., E. melonii sp. nov., Leptotyphlus nardii sp. nov., L. minator sp. nov. and L. villacidrinus sp. nov.; all are easily distinguishable from their congeners by the structure of the male copulatory organ and female genital armature. The morphology of the copulatory organ in the newly described Leptotyphlus species indicates that the classical subgeneric categories used in Leptotyphlus are probably based on characters not reflecting a natural subdivision of the genus.